HCA Holdings, Inc. : for-profit medicine and unnecessary surgery - Nielsen, Sister Petra (Catherine) (SAGE Knowledge. Cases., 2017)
On August 6, 2012, HCA Holdings, Inc., one of the largest for-profit hospital management companies in America, revealed to investors that the U.S. Attorneys Office in Miami had requested documents related to unnecessary cardiac procedures at ten of its hospitals. HCA's announcement coincided with an article published by The New York Times on the investigation. HCA is the largest hospital management company in America and has had a history of legal issues ranging from Medicare fraud to unnecessary heart procedures.